The Avatar Effect: The harmful consequences of decision-making through a 'separate' entity. - Macdonald, Chris (Open Science Journal, 2020)
As we are in the midst of a global crisis, caused primarily by human activity, it is vital to ask, what leads us to make such ethically compromised decisions? This paper reveals a phenomenon that may cause an individual to loosen or lose their moral compass: the avatar effect. The case is made that there are frequent situations where individuals can make decisions through—what appears to them as—a separate entity, and that through compounding underlying mechanisms, this can result in an increased sense of disconnection, compromised judgement, and harmful consequences.